Caatinga Overland Flow Hydraulics: How Shrubs in the Brazilian Semi-Arid Environment Interact with Overland Flow - Cicero Gomes dos Santos; Jose Ramon B. Cantalice; Guilherme Santiago M. Cantalice; Juliano P. Sena Sousa; Ailton Alves de Carvalho; Daniel Moura Silva (Environmental Processes, 2026)
Hydraulic implications occur when rainfall and overland flow move across the vegetative structure of the Caatinga, the shrubland native to Brazil’s semi-arid region, which is a climate change hotspot. Can the Caatinga structure’s effects on rain interception, along with water retention caused by hydraulic resistance, significantly increase water infiltration? How can overland flow at low Reynolds numbers be affected? Twelve simulated rain events were conducted in a Brazilian semi-arid watershed, focusing on these questions in a degraded Caatinga area also used for growing semi-arid crops. The entire Caatinga vegetation and litter reduced flow velocity by 55.24% and 60.55%, respectively, and increased hydraulic resistance by 68.64% and 61.18%, respectively, compared to bare soil conditions. Hydraulic resistance was governed by the Froude number, as shown by a very good exponential decay function with a very high coefficient of determination (R 2 = 0.9902). Caatinga’s structural vegetative elements, such as litter (fallen leaves on the soil surface), and the entire Caatinga structure increase hydraulic resistance, providing an efficient environmental protection against overland flow. Therefore, even under the stress conditions of the dry season, Caatinga, as part of the semi-arid ecosystem, remains alive and ecologically active, responding hydraulically to overland flow.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Environmental resistance parameters generated by soil and semi-arid crops under inter-rill erosion and overland flow with low Reynolds numbers - Jose Ramon B. Cantalice; Francisco Manuel de Assis Filho; Genival Barros Junior; Clara Barros Mendes Cantalice; Kalinny Patricia Lafayette; Jonas da Silva Bezerra; Joyce Ingrid de Arandas Sobral; Luciana Cássia Lima da Silva; Luan Carlos De Andrade Santos; Bruno Jose Silva de Medeiros; Daniel Moura Silva; Cicero Gomes dos Santos (CATENA, 2026)

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Neuroinflammation and RAMP1: the Role of the Peripheral and Central Nervous System in Tumor Progression - Pedro Daniel Moumesso Cavalcante; Jonas Lucas Dias da Silva; Laryssa Rosy Santos Oliveira; Rikelly Barbosa da Silva; Juliana Acioli Costa Lima; Guilherme de Brito Souza; Davi Ramon da Silva Santos; Júllia Victória Nascimento de Abrantes; Mateus Lima de Farias; Sofia Amancio de Almeida Oliveira; João Paulo Emiliano da Silva; Rafael de Oliveira Calaça Farias; et al. (Cell Biochemistry and Biophysics, 2026)
Calcitonin gene-related peptide (CGRP) and receptor activity modifier protein 1 (RAMP1) form a critical neuroimmunoendocrine axis in the modulation of neuroinflammation, pain, and tumor progression. CGRP, released by sensory and sympathetic fibers, is a potent vasodilator and nociceptive modulator; its action depends on the receptor composed of CALCRL and RAMP1. In the central nervous system, the activation of microglia and astrocytes and the induction of pathways such as NF-κB and MAPK culminate in the production of proinflammatory cytokines (TNF-α, IL-6), differing from systemic inflammation due to the presence of the blood-brain barrier and the glial microenvironment. Preclinical evidence demonstrates RAMP1 expression in neurons, glial cells, endothelium, and macrophages; CGRP/RAMP1 signaling promotes vascular permeability, cytokine release, and angiogenesis, potentially synergizing with VEGF. In animal models and cell cultures, genetic or pharmacological manipulations of the axis reduce tumor angiogenesis, pro-tumor immune infiltration, tumor growth, and nociceptive behavior. Given the clinical availability of CGRP antagonists and monoclonal antibodies, blocking the CGRP/RAMP1 axis is a promising translational strategy for modulating tumor progression and cancer pain. This review summarizes preclinical evidence on mechanisms and therapeutic feasibility. The article includes preclinical and clinical safety and biomarker studies.

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Genotypic Behaviour of Sugarcane Clones for Juice Quality and Bagasse Composition - Ana Beatriz De-Freitas; Luiz Daniel Da-Silva; Maria Clara De-Barros; Túlio Leite; Ramon Freire Da-Silva; Normando Ribeiro-Filho; Fábio Mielezrski (Tropical Plant Biology, 2025)

Neuroprotective Role of Ketamine in Reducing Neuroinflammation and Enhancing Neuroplasticity Against a Cortisol-Induced In Vitro Stress Model - Lucas Santos; Fernanda dos Santos Petry; Carolina Saibro-Girardi; Júlia Hansen; Danielle Martins; Nicole Fröhlich; Luana Possa; Luiz Filipe Bastos Mendes; Hémelin Resende Farias; Alberto Martins Silva; Izabbela Giacon Deitos; Reykla Ramon Bittencourt; et al. (Molecular Neurobiology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Advances in postharvest nanotechnology: Enhancing fresh produce shelf life and quality to reduce losses and waste - Yuru Chang; Marcos David Ferreira; Daniel Souza Correa; Kelcilene Bruna Ricardo Teodoro; Fernanda Ramalho Procopio; Ramon Peres Brexó; Ali Sarkhosh; Jeffrey K. Brecht (Postharvest Biology and Technology, 2025)

Cloud processing dominates the vertical profiles of aerosols in marine air masses over the Great Barrier Reef - Ramon C. Braga; Daniel Rosenfeld; Diana Hernandez; Chris Medcraft; Avichay Efraim; Manuel Moser; Johannes Lucke; Adrian Doss; Daniel Harrison (Atmospheric Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Compound effects of drought and COVID-19 on soybean production in Brazil: Challenges and policy responses - Ramon Felipe Bicudo da Silva; Andrés Viña; Daniel de Castro Victoria; Mateus Batistella; Geraldo B. Martha; Emilio Federico Moran; Jianguo Liu (Science of The Total Environment, 2025)

Comparative population genomics of manta rays has global implications for management - Emily Humble; Jane Hosegood; Gary Carvalho; Mark de Bruyn; Simon Creer; Guy M. W. Stevens; Amelia Armstrong; Ramon Bonfil; Mark Deakos; Daniel Fernando; Niv Froman; Lauren R. Peel; et al. (Molecular Ecology, 2025)
Understanding population connectivity and genetic diversity is of fundamental importance to conservation. However, in globally threatened marine megafauna, challenges remain due to their elusive nature and wide‐ranging distributions. As overexploitation continues to threaten biodiversity across the globe, such knowledge gaps compromise both the suitability and effectiveness of management actions. Here, we use a comparative framework to investigate genetic differentiation and diversity of manta rays, one of the most iconic yet vulnerable groups of elasmobranchs on the planet. Despite their recent divergence, we show how oceanic manta rays ( Mobula birostris ) display significantly higher heterozygosity than reef manta rays ( Mobula alfredi ) and that M. birostris populations display higher connectivity worldwide. Through inferring modes of colonization, we reveal how both contemporary and historical forces have likely influenced these patterns, with important implications for population management. Our findings highlight the potential for fisheries to disrupt population dynamics at both local and global scales and therefore have direct relevance for international conservation of marine species.

Caatinga diaspores: Descriptive overview of dispersal units of seasonally dry tropical forests and woodlands - Fabricio Francisco Santos da Silva; Edjane Silva Damasceno; Ramon Athayde de Souza Cavalcante; Francinete Alves do Nascimento; Mateus Brandão Prates; Luís Francisco Mello Coelho; Daniel Salgado Pifano; Renato Garcia Rodrigues (Ecology, 2025)
Dispersal unit characteristics provide crucial insights into species ecology and are essential for the conservation and restoration of ecosystems. The Caatinga, the largest ecosystem of seasonally dry tropical forests and woodlands in South America, remains underrepresented in terms of dispersal unit data, which are often scattered across the scientific literature or remain unpublished. To address this gap, we compiled a dataset of morphophysiological data for 100 native taxa, including key information such as germination, seed water content, 1000 seed mass, fruit shape, and the geographic coordinates of 1981 seed lots. Over nine years, more than 60 t of dispersal units were harvested, representing 91% of the most dominant woody species in this ecosystem. These records stem from environmental licensing actions associated with the São Francisco River Integration Project (PISF), the Re‐Habitar Ararinha Azul Project, and verified literature. This dataset, the first of its kind for the Caatinga, offers valuable potential for research on forest dynamics, dispersal, germination, conservation, and ecological restoration in the Brazilian semiarid region. We hope this data paper provides reliable information on local flora distribution, dispersal syndromes, and morphological descriptions, while also suggesting methods for overcoming seed dormancy in the Caatinga. No copyright restrictions apply to this dataset, but please cite this data paper in publications. We also encourage researchers and educators to inform us of how they are using the data.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

From waste to advanced resource: Techno-economic and life cycle assessment behind the integration of polyester recycling and glucose production to valorize fast fashion garments - Ramon E. Vera; Keren A. Vivas; Naycari Forfora; Ronald Marquez; Isabel Urdaneta; Ryen Frazier; Camilla Abbati de Assis; Tiago de Assis; Trevor Treasure; Matthew Farrell; Mary Ankeny; Daniel Saloni; et al. (Chemical Engineering Journal, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Artificial intelligence strategies applied in general and automotive air conditioning control. A review of the last 20 years - Ramon de Paoli Mendes; Juan José Garcia Pábon; Daniel Leon Ferreira Pottie; Luiz Machado (International Journal of Refrigeration, 2024)

Cannabidiol disrupts tryptophan metabolism in the human term placenta - Ramon Portillo; Cilia Abad; Tetiana Synova; Petr Kastner; Daniel Heblik; Radim Kucera; Rona Karahoda; Frantisek Staud (Toxicology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Secondary droplet activation during condensational growth in convective clouds and its detection from satellites - Avichay Efraim; Ramon C. Braga; Daniel Rosenfeld; Oliver Lauer; Marco A. Franco; Leslie A. Kremper; Christopher Pöhlker; Meinrat O. Andreae; Cléo Q. Dias-Junior; Mira L. Pöhlker (Atmospheric Research, 2024)

Transgenerational inheritance of methylmercury and vitamin A-induced toxicological effects in a Wistar rats environmental-based model - Flávio Gabriel Carazza-Kessler; Marlene Soares Campos; Reykla Ramon Bittencourt; Helen Taís da Rosa-Silva; Pedro Ozorio Brum; Alexandre Kléber Silveira; Alexsander Alves Teixeira; Camila Tiefensee Ribeiro; Daniel Oppermann Peixoto; Lucas Santos; Giovanni Andrade; Alana Castro Panzenhagen; et al. (Chemosphere, 2024)

Field demonstration for the solvent-based sampling method to perform compound-specific isotope analysis on gas-phase VOC - Daniel Bouchard; Daniel Hunkeler; Massimo Marchesi; Ramon Aravena; Tim Buscheck (Journal of Contaminant Hydrology, 2024)

Genetic selection for high growth improves the efficiency of gilthead sea bream (Sparus aurata) in using novel diets with insect meal, single-cell protein and a DHA rich-microalgal oil - Marta Carvalho; Rafael Ginés; Ignacio Martín; María Jesús Zamorano; Félix Acosta; Ramon Fontanillas; Silvia Torrecillas; Daniel Montero (Aquaculture, 2024)

Differential apicomplexan presence predicts thermal stress mortality in the Mediterranean coral Paramuricea clavata - Anthony M. Bonacolta; Jordi Miravall; Daniel Gómez‐Gras; Jean‐Baptiste Ledoux; Paula López‐Sendino; Joaquim Garrabou; Ramon Massana; Javier del Campo (Environmental Microbiology, 2024)
Paramuricea clavata is an ecosystem architect of the Mediterranean temperate reefs that is currently threatened by episodic mass mortality events related to global warming. The microbiome may play an active role in the thermal stress susceptibility of corals, potentially holding the answer as to why corals show differential sensitivity to heat stress. To investigate this, the prokaryotic and eukaryotic microbiome of P. clavata collected from around the Mediterranean was characterised before experimental heat stress to determine if its microbial composition influences the thermal response of the holobiont. We found that members of P. clavata's microeukaryotic community were significantly correlated with thermal stress sensitivity. Syndiniales from the Dino‐Group I Clade 1 were significantly enriched in thermally resistant corals, while the apicomplexan corallicolids were significantly enriched in thermally susceptible corals. We hypothesise that P. clavata mortality following heat stress may be caused by a shift from apparent commensalism to parasitism in the corallicolid‐coral host relationship driven by the added stress. Our results show the potential importance of corallicolids and the rest of the microeukaryotic community of corals to understanding thermal stress response in corals and provide a useful tool to guide conservation efforts and future research into coral‐associated microeukaryotes.

Transforming non-wood feedstocks into dissolving pulp via organosolv pulping: An alternative strategy to boost the share of natural fibers in the textile industry. - Ramon E. Vera; Keren A. Vivas; Fernando Urdaneta; Jorge Franco; Runkun Sun; Naycari Forfora; Ryen Frazier; Stephanie Gongora; Daniel Saloni; Larissa Fenn; J.Y. Zhu; Hou-min Chang; et al. (Journal of Cleaner Production, 2023)

Embodied greenhouse gas emissions in structural materials for the German residential building stock — Quantification and mitigation scenarios - Ramon Hingorani; Nils Dittrich; Jochen Köhler; Daniel B. Müller (Building and Environment, 2023)

Using structure-from-motion to estimate cover crop biomass and characterize canopy structure - April M. Dobbs; Daniel Ginn; Søren Kelstrup Skovsen; Ramawatar Yadav; Prashant Jha; Muthukumar V. Bagavathiannan; Steven B. Mirsky; Chris S. Reberg-Horton; Ramon G. Leon (Field Crops Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

White mustard (Sinapis alba L.) residues with enhanced potential as soil biofumigant by using controlled elicitation during cultivation - Marcela Vargas-Hernandez; Daniel A. Arriaga-Madrid; Alejandra Cortez-Perez; Ana A. Feregrino-Perez; Maria G. Ortega-Salazar; Angel G. Alpuche-Solis; Irineo Torres-Pacheco; Francois Gautier; Ramon G. Guevara-Gonzalez (European Journal of Plant Pathology, 2023)

Multistimuli-responsive smart windows based on paraffin-polymer composites - Jaume Ramon Otaegui; Daniel Ruiz-Molina; Jordi Hernando; Claudio Roscini (Chemical Engineering Journal, 2023)

The surface-boundary layer connection across spatial scales of irrigation-driven thermal heterogeneity: An integrated data and modeling study of the LIAISE field campaign - Mary Rose Mangan; Oscar Hartogensis; Aaron Boone; Oliver Branch; Guylaine Canut; Joan Cuxart; Hugo J. de Boer; Michel Le Page; Daniel Martínez-Villagrasa; Josep Ramon Miró; Jeremy Price; Jordi Vilà-Guerau de Arellano (Agricultural and Forest Meteorology, 2023)

Ecological carrying capacity in mariculture: Consideration and application in geographic strategies and policy - Jeffrey Fisher; Dror Angel; Myriam Callier; Daniel Cheney; Ramon Filgueira; Bobbi Hudson; Christopher W. McKindsey; Lisa Milke; Heather Moore; Francis O’Beirn; Jack O’Carroll; Berit Rabe; et al. (Marine Policy, 2023)

The phylogenomics and evolutionary dynamics of the organellar genomes in carnivorous Utricularia and Genlisea species (Lentibulariaceae) - Saura R. Silva; Vitor F.O. Miranda; Todd P. Michael; Bartosz J. Płachno; Ramon G. Matos; Lubomir Adamec; Sergei L.K. Pond; Alexander G. Lucaci; Daniel G. Pinheiro; Alessandro M. Varani (Molecular Phylogenetics and Evolution, 2023)

Insect and single-cell protein meals as replacers of fish meal in low fish meal and fish oil diets for gilthead sea bream (Sparus aurata) juveniles - Marta Carvalho; Silvia Torrecillas; Daniel Montero; Antonio Sanmartín; Ramon Fontanillas; Ana Farías; Katerina Moutou; Jorge Hernández Velásquez; Marisol Izquierdo (Aquaculture, 2023)

Temperature modulates gonadal development and sex ratio of pirancanjuba Brycon orbignyanus - Helena Robattini Carvalho; Diógenes Henrique de Siqueira-Silva; Rômulo Batista Rodrigues; Louise Nex Spica; Daniel Antonio Rotili; Éverton Luís Zardo; Andrea Giannotti Galuppo; Renata Villar; Juan Ramon Esquivel-Muelbert; Jayme Aparecido Povh; Leonardo Barcellos; Danilo Pedro Streit (Aquaculture, 2023)

Comparison of effects of a single dose of MHYOSPHERE® PCV ID with three commercial porcine vaccine associations against Mycoplasma hyopneumoniae (Mhyo) and porcine circovirus type 2 (PCV2) on piglet growth during the nursery period under field conditions - Ainhoa Puig; Ignacio Bernal; David Sabaté; Isaac Ballarà; Jordi Montané; Lorena Nodar; Daniel Angelats; Ramon Jordà (Veterinary Research Communications, 2022)
Pigs routinely undergo stressful vaccination procedures, which are often unavoidable given the unavailability of safer alternatives, challenging animal welfare. The available vaccines for Mycoplasma hyopneumoniae (Mhyo) or Porcine circovirus type 2 (PCV2) are mostly administered intramuscularly in association to prevent Porcine respiratory disease complex (PRDC). MHYOSPHERE® PCV ID is the first vaccine protecting from both agents by intradermal route. This randomized, blind-field trial aimed to compare the effects of MHYOSPHERE® PCV ID with those of three different intramuscular associations of commercially available vaccines. A total of 7072 21-day-old piglets from 12 consecutive batches in one farm were randomly vaccinated with MHYOSPHERE® PCV ID (G1) or Ingelvac CircoFLEX® + Hyogen® (G2), Porcilis® PCV + M + PAC® (G3), and Porcilis® PCV + Hyogen® (G4). Growth performance during the nursery period and adverse reactions (ARs) after vaccine administration were monitored. Average Daily Weight Gain (ADWG) during the first 7 days post-weaning in G1 was 10.92, 3.03, and 20.08 g/day higher than in G2, G3, and G4, respectively, and 0.65, 4.06, and 9.58 g/day higher than in G2, G3, and G4 during the entire nursery period, respectively. G1 ADWG was significantly higher than G4 during both periods and significantly higher than G2 during the first 7 days post-weaning. Incidence of systemic ARs in G2 and G4 was 0.03% and 0.32%, respectively; none were recorded in G1 and G3. Replacing the usual intramuscular vaccination with MHYOSPHERE® PCV ID results in higher growth performance during the first weeks after weaning with no systemic ARs.

Water demand of central pivot-irrigated areas in Bahia, Brazil: management of water resources applied to sustainable production - Wilian Rodrigues Ribeiro; Morgana Scaramussa Gonçalves; Daniel Soares Ferreira; Dalila da Costa Gonçalves; Samira Luns Hatum de Almeida; Ramon Amaro de Sales; Felipe Cunha Siman; Luan Peroni Venancio; Edvaldo Fialho dos Reis (Environment, Development and Sustainability, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Using plant growth-promoting microorganisms (PGPMs) to improve plant development under in vitro culture conditions - Daniel Cantabella; Ramon Dolcet-Sanjuan; Neus Teixidó (Planta, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Rhizosphere microorganisms enhance in vitro root and plantlet development of Pyrus and Prunus rootstocks - Daniel Cantabella; Neus Teixidó; Guillem Segarra; Rosario Torres; Maria Casanovas; Ramon Dolcet-Sanjuan (Planta, 2021)

Phylogenomics and species delimitation for effective conservation of manta and devil rays - Jane Hosegood; Emily Humble; Rob Ogden; Mark de Bruyn; Simon Creer; Guy M. W. Stevens; Mohammed Abudaya; Kim Bassos‐Hull; Ramon Bonfil; Daniel Fernando; Andrew D. Foote; Helen Hipperson; et al. (Molecular Ecology, 2020)
Practical biodiversity conservation relies on delineation of biologically meaningful units. Manta and devil rays (Mobulidae) are threatened worldwide, yet morphological similarities and a succession of recent taxonomic changes impede the development of an effective conservation strategy. Here, we generate genome‐wide single nucleotide polymorphism (SNP) data from a geographically and taxonomically representative set of manta and devil ray samples to reconstruct phylogenetic relationships and evaluate species boundaries under the general lineage concept. We show that nominal species units supported by alternative data sources constitute independently evolving lineages, and find robust evidence for a putative new species of manta ray in the Gulf of Mexico. Additionally, we uncover substantial incomplete lineage sorting indicating that rapid speciation together with standing variation in ancestral populations has driven phylogenetic uncertainty within Mobulidae. Finally, we detect cryptic diversity in geographically distinct populations, demonstrating that management below the species level may be warranted in certain species. Overall, our study provides a framework for molecular genetic species delimitation that is relevant to wide‐ranging taxa of conservation concern, and highlights the potential for genomic data to support effective management, conservation and law enforcement strategies.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The importance of naturally attenuated SARS‐CoV ‐2 in the fight against COVID ‐19 - Jean Armengaud; Agnès Delaunay‐Moisan; Jean‐Yves Thuret; Eelco van Anken; Diego Acosta‐Alvear; Tomás Aragón; Carolina Arias; Marc Blondel; Ineke Braakman; Jean‐François Collet; René Courcol; Antoine Danchin; et al. (Environmental Microbiology, 2020)
The current SARS‐CoV‐2 pandemic is wreaking havoc throughout the world and has rapidly become a global health emergency. A central question concerning COVID‐19 is why some individuals become sick and others not. Many have pointed already at variation in risk factors between individuals. However, the variable outcome of SARS‐CoV‐2 infections may, at least in part, be due also to differences between the viral subspecies with which individuals are infected. A more pertinent question is how we are to overcome the current pandemic. A vaccine against SARS‐CoV‐2 would offer significant relief, although vaccine developers have warned that design, testing and production of vaccines may take a year if not longer. Vaccines are based on a handful of different designs (i), but the earliest vaccines were based on the live, attenuated virus. As has been the case for other viruses during earlier pandemics, SARS‐CoV‐2 will mutate and may naturally attenuate over time (ii). What makes the current pandemic unique is that, thanks to state‐of‐the‐art nucleic acid sequencing technologies, we can follow in detail how SARS‐CoV‐2 evolves while it spreads. We argue that knowledge of naturally emerging attenuated SARS‐CoV‐2 variants across the globe should be of key interest in our fight against the pandemic.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Cold‐air pool evolution in a wide Pyrenean valley - Laura Conangla; Joan Cuxart; Maria Antonia Jiménez; Daniel Martínez‐Villagrasa; Josep Ramon Miró; Davide Tabarelli; Dino Zardi (International Journal of Climatology, 2018)
This study on cold‐air pool formation in the wide Cerdanya Valley in the Pyrenees mountain range was conducted using available observational information from September 2010 to August 2014. Cold‐air pools occur during almost 60% of the nights, mainly during winter. Cold pools develop even under significant synoptic pressure gradients. Additionally, drainage currents transporting air down‐valley occur most of the nights. In particular one representative cold‐air pool event has been analysed in detail by a high‐resolution mesoscale simulation, combined with an analysis of data from both ground‐based stations and satellites. Radiative processes dominate the evolution of cold‐air pools, together with turbulence in the lowest layers, while drainage flows down from the high mountains mainly through the tributary valleys and from the valley sidewall slopes play a key role in bringing air to the pool. Cold pool formation begins approximately 1 hr after sunset, and it extends across most of the valley bottom, with a very strong thermal inversion close to the surface that has a depth of up to 100 m in the lowest parts of the valley. Wind veers down‐valley along the main axis 2–3 hr after sunset and the wind direction is approximately maintained until after sunrise.

Erratum to: Considering total intracranial volume and other nuisance variables in brain voxel based morphometry in idiopathic PD - Samuel Crowley; Haiqing Huang; Jared Tanner; Qing Zhao; Nadine A. Schwab; Loren Hizel; Daniel Ramon; Babette Brumback; Mingzhou Ding; Catherine C. Price (Brain Imaging and Behavior, 2018)

Considering total intracranial volume and other nuisance variables in brain voxel based morphometry in idiopathic PD - Samuel Crowley; Haiqing Huang; Jared Tanner; Qing Zhao; Nadine A. Schwab; Loren Hizel; Daniel Ramon; Babette Brumback; Mingzhou Ding; Catherine C. Price (Brain Imaging and Behavior, 2018)

Integrating Science-Based Co-management, Partnerships, Participatory Processes and Stewardship Incentives to Improve the Performance of Small-Scale Fisheries - Kendra A. Karr; Rod Fujita; Ramon Carcamo; Lawrence Epstein; James R. Foley; José A. Fraire-Cervantes; Mauro Gongora; Ollin T. Gonzalez-Cuellar; Pablo Granados-Dieseldorff; Julius Guirjen; Amy H. Weaver; Héctor Licón-González; et al. (Frontiers in Marine Science, 2017)

Differential Gene Expression in Liver, Gill, and Olfactory Rosettes of Coho Salmon (Oncorhynchus kisutch) After Acclimation to Salinity - Lindley A. Maryoung; Ramon Lavado; Theo K. Bammler; Evan P. Gallagher; Patricia L. Stapleton; Richard P. Beyer; Federico M. Farin; Gary Hardiman; Daniel Schlenk (Marine Biotechnology, 2015)

Effect of Simultaneous Administration of Dihydroxyacetone on the Diffusion of Lawsone Through Various In Vitro Skin Models - Daniel J. Munt; Anne Grana; Martin Hulce; Ramon M. Fusaro; Alekha K. Dash (AAPS PharmSciTech, 2015)

Marine protist diversity in E uropean coastal waters and sediments as revealed by high‐throughput sequencing - Ramon Massana; Angélique Gobet; Stéphane Audic; David Bass; Lucie Bittner; Christophe Boutte; Aurélie Chambouvet; Richard Christen; Jean‐Michel Claverie; Johan Decelle; John R. Dolan; Micah Dunthorn; et al. (Environmental Microbiology, 2015)
Summary Although protists are critical components of marine ecosystems, they are still poorly characterized. Here we analysed the taxonomic diversity of planktonic and benthic protist communities collected in six distant E uropean coastal sites. Environmental deoxyribonucleic acid ( DNA ) and ribonucleic acid ( RNA ) from three size fractions (pico‐, nano‐ and micro/mesoplankton), as well as from dissolved DNA and surface sediments were used as templates for tag pyrosequencing of the V4 region of the 18S ribosomal DNA. Beta‐diversity analyses split the protist community structure into three main clusters: picoplankton‐nanoplankton‐dissolved DNA , micro/mesoplankton and sediments. Within each cluster, protist communities from the same site and time clustered together, while communities from the same site but different seasons were unrelated. Both DNA and RNA ‐based surveys provided similar relative abundances for most class‐level taxonomic groups. Yet, particular groups were overrepresented in one of the two templates, such as marine alveolates ( MALV )‐ I and MALV‐II that were much more abundant in DNA surveys. Overall, the groups displaying the highest relative contribution were Dinophyceae, Diatomea, Ciliophora and Acantharia. Also, well represented were Mamiellophyceae, Cryptomonadales, marine alveolates and marine stramenopiles in the picoplankton, and Monadofilosa and basal F ungi in sediments. Our extensive and systematic sequencing of geographically separated sites provides the most comprehensive molecular description of coastal marine protist diversity to date.

Effects of salinity acclimation on the expression and activity of Phase I enzymes (CYP450 and FMOs) in coho salmon (Oncorhynchus kisutch) - Ramon Lavado; Rosaura Aparicio-Fabre; Daniel Schlenk (Fish Physiology and Biochemistry, 2014)

Global phylogeography of marine Synechococcus and Prochlorococcus reveals a distinct partitioning of lineages among oceanic biomes - Katrin Zwirglmaier; Ludwig Jardillier; Martin Ostrowski; Sophie Mazard; Laurence Garczarek; Daniel Vaulot; Fabrice Not; Ramon Massana; Osvaldo Ulloa; Dave J. Scanlan (Environmental Microbiology, 2008)
Summary Marine cyanobacteria of the genera Prochlorococcus and Synechococcus are important contributors to global primary production occupying a key position at the base of marine food webs. The genetically diverse nature of each genus is likely an important reason for their successful colonization of vast tracts of the world's oceans, a feature that has led to detailed analysis of the distribution of these genetic lineages at the local and ocean basin scale. Here, we extend these analyses to the global dimension, using new data from cruises in the Pacific, Indian and Arctic Oceans in combination with data from previous studies in the Atlantic Ocean, Arabian Sea, Red Sea and a circumnavigation of the southern hemisphere to form a data set which comprises most of the world's major ocean systems. We show that the distribution patterns of Prochlorococcus and Synechococcus lineages are remarkably similar in different ocean systems with comparable environmental conditions, but producing a strikingly different ‘signature’ in the four major ocean domains or biomes (the Polar Domain, Coastal Boundary Domain, Trade Winds Domain and Westerly Winds Domain). This clearly reiterates the idea of spatial partitioning of individual cyanobacterial lineages, but at the global scale.

Transgenic wine yeast technology comes of age: is it time for transgenic wine? - Eduardo Cebollero; Daniel Gonzalez-Ramos; Laura Tabera; Ramon Gonzalez (Biotechnology Letters, 2007)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)